Correlates of externalising and internalising problems in children with dyslexia: An analysis of data from clinical casefiles - Boyes, Mark; Leitao, Suze; Claessen, Mary; Badcock, N.A.; Nayton, M. (2019)
© 2019 The Australian Psychological Society Objective: Adopting a socio-ecological perspective, we used data extracted from clinical casefiles to investigate factors associated with externalising and internalising problems in a large, representative sample of children with a diagnosis of dyslexia. Method: This study is a secondary analysis of data collected by the Dyslexia-SPELD Foundation in Western Australia. Casefiles for school-aged children who had received a dyslexia diagnosis in 2014 and 2015 were identified (n = 1,235), and a subset of casefiles were randomly selected for data extraction (n = 454). Of the sample, 58% (n = 262) were male, 42% (n = 192) were female. Ages ranged between 6 and 17 years (M = 12.32, SD = 3.07). Casefiles include results from assessments of literacy-related achievement, as well as parent-reported information on behavioural and socio-emotional development. Results: After controlling for child age, gender, and reading ability, it was found that low self-esteem, difficulties in emotion regulation, and social skills difficulties were all associated with externalising problems. Additionally, low self-esteem, difficulties in emotion regulation, and bullying victimisation were all associated with internalising problems. Peer relationship difficulties were indirectly associated with both externalising and internalising problems through associations with low self-esteem and difficulties in emotion regulation. Conclusion: Self-esteem, bullying victimisation, emotion regulation, social skills, and peer problems are salient correlates of externalising and internalising problems in children with a diagnosis of dyslexia. Implications for intervention are discussed, both universal school-based mental health promotion programs, as well as more targeted programs for children with dyslexia.